Practice of offender profiling in Japan - Yokota, Kaeko (International journal of police science & management, 2017)
The main aim of this study was to determine the current situation of offender profiling in Japan. In addition, the accuracy of crime linkage and inferring offenders’ profiles were examined. To evaluate offender profiling comprehensively, we conducted a national survey of 156 people responsible for offender profiling between 2011 and 2012 to obtain their demographic characteristics and experience related to profiling. Furthermore, we also used a sample of 296 resolved cases to examine the content of profiling and the accuracy of predictions in offender profiling. The results of the statistical analyses revealed that police professionals from various backgrounds were engaged in profiling in Japan; 76% were police investigators, and 19% were professionals at forensic science laboratories engaged in psychological work. Regarding the utilization of profiling results in police investigations, 46% of profiling ‘led to identification of offender’. As for prediction accuracy, the rate of linkage errors (i.e. where profilers could not correctly link incidents even when they knew of the occurrence of these incidents) was 15%. Accurately inferring an offender’s profile was found to be between 72% (means of transportation) and 100% (sex). We also discussed the challenges faced by the police who practise offender profiling in Japan.